Pascu-type p-valent functions associated with the convolution structure - ÖNER, Birgül; SÜMER EKER, Sevtap (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
Making use of convolution structure, we introduce a new class of pvalent functions. Among the results presented in this paper include the coecient bounds, distortion inequalities, extreme points and integral means inequalities for this generalized class of functions are discussed. Mathematics Subject Classification (2010): 30C45, 30C50.